2021
DOI: 10.1101/2021.07.01.21259887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 infection and hospitalisation in children and adolescents in Norway: A nationwide population-based study

Abstract: Objective: To determine risk factors for SARS-CoV-2 infection and hospitalisation among children and adolescents. Design: Nationwide, population-based cohort study. Setting: Norway from 1 March 2020 to 31 April 2021. Participants: All Norwegian residents <18 years of age. Main outcome measures: Population-based health care and population registries were used to study risk factors for SARS-CoV-2 infection, including socioeconomic factors, country of origin, and pre-existing chronic comorbidities. All reside… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Our findings indicated that although all the included three cases with the co-infection were hospitalized, none of them developed severe outcomes and were discharged after a good recovery. Accordingly, these findings showed that patients having COVID-19 and MPV co-infection might not develop severe outcomes since all the included patients also had multiple comorbid conditions, which were previously reported as significant risk factors for developing severe COVID-19 outcomes ( 2 ). To our knowledge, COVID-19 infection presents usually with fever, cough, fever and smell and tasting disorders.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Our findings indicated that although all the included three cases with the co-infection were hospitalized, none of them developed severe outcomes and were discharged after a good recovery. Accordingly, these findings showed that patients having COVID-19 and MPV co-infection might not develop severe outcomes since all the included patients also had multiple comorbid conditions, which were previously reported as significant risk factors for developing severe COVID-19 outcomes ( 2 ). To our knowledge, COVID-19 infection presents usually with fever, cough, fever and smell and tasting disorders.…”
mentioning
confidence: 53%
“…COVID-19 still constitutes a remarkable burden on countries and their healthcare systems even with the remarkable advances in the vaccine industry. COVID-19 patients are liable to various complications, and those with co-morbidities and associated infections are usually the most vulnerable ( 1 , 2 ). Recently, a multi-country outbreak of monkeypox virus (MPV) occurred and the World Health Organization declared it a Public Health Emergency of International Concern.…”
mentioning
confidence: 99%
“…However, studies show that other air pollutants, i.e., nitrogen oxides and ozone, may also affect the COVID-19 severity and mortality ( Mele et al, 2021 , Khorsandi et al, 2021 , Achebak et al, 2021 ). One should also note that the present investigation did not include the potential differences in socioeconomic factors, health behaviors (e.g., physical activity) and presence of comorbidities (e.g., chronic lung disease, diabetes, heart disease, immune deficiencies, seizure disorders, obesity,) that may affect the susceptibility of children to COVID-19 ( Choi et al, 2022 , Størdal et al, 2022 ). Moreover, the patient data were collected over 17 months, during which various SARS-CoV-2 variants emerged and dominated ( Hryhorowicz et al, 2021 , Jabłońska et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%